THE LINGUOPOETICS OF JOHN STEINBECK’S WORKS (Scientific journal of the Fergana State University, 2025)
The article discusses the writing style of the great American writer John Steinbeck. The author analyses the linguopoetic peculiarities of his novels, especially in the novel called “The grapes of wrath”. Furthermore, stylistic devices and expressive means, grammatical deviation are investigated thoroughly following the linguopoetic approaches. The article emphasizes the quintessential contributions of John Steinbeck in terms of library language and English literature. There is a lot of information about the innovations and novelty of the writer by expressing the cultural, social and scientific information regarding the nation, nature and geographic location of the country.The research paper highlights the linguistic devices such as apocope, syncope and apheresis to create mystery and rhythm in the novel. By scrutinizing the oral speech patterns and non-standard lexicon and the structure, the author intends to identify the writing skills of John Steinbeck. Finally, there is a conclusion on recognizing Steinbeck’s substantial contribution to the development of modern English by his unparalleled literary legacy.